Species Diversity and Seasonal Variation of Butterfly Fauna in Thankot and Syuchatar VDC of Kathmandu Valley, Nepal - Thapa, Gita; Bhusal, Daya Ram (Journal of Natural History Museum, 2009)
Diversity of butterfly was studied in Thankot and Syuchatar VDCs of Kathmandu District, during June 2007-March 2008. A total of 43 species of butterflies belonging to 32 genera and 9 families were recorded with Nymphalidae as the most commonly recorded family and Libytheidae and Acreidae are the least represented families. The species were collected in summer and winter seasons. Bushes, cultivated land, open field and forest were selected to study the habitats of butterflies. Bushes were found to be the most preferable habitat. Seasonal variation was also observed in some species. Three species namely Ypthima baldus, Ypthima nareda and Precis iphita showed color variation. Troides aeacus, a CITES listed species was also observed in this region. Key words: Acreidae; Libytheidae; Nymphalidae; Seasonal variation; Troides aeacus.. Journal of Natural History Museum Vol. 24, 2009, Page: 9-15